Ventricular Fibrosis and Coronary Remodeling Following Short-Term Exposure of Healthy and Malnourished Mice to Bisphenol A - García-Arévalo, Marta; Lorza-Gil, Estela; Cardoso, Leandro; Batista, Thiago Martins; Araujo, Thiago Reis; Ramos, Luiz Alberto Ferreira; Areas, Miguel Arcanjo; Nadal, Angel; Carneiro, Everardo Magalhães; Davel, Ana Paula (Frontiers in Physiology, 2021)
Bisphenol-A (BPA) is an endocrine disruptor associated with higher risk of insulin resistance, type 2 diabetes, and cardiovascular diseases especially in susceptible populations. Because malnutrition is a nutritional disorder associated with high cardiovascular risk, we sought to compare the effects of short-term BPA exposure on cardiovascular parameters of healthy and protein-malnourished mice. Post-weaned male mice fed a normo- (Control) or low-protein (LP) diet for 8 weeks and then were exposed or not to BPA (50 µg/kg/day) for the last 9 days. Systolic blood pressure was higher in BPA or LP groups compared to control group. However, diastolic blood pressure was enhanced by BPA only in malnourished mice. Left ventricle (LV) end diastolic pressure (EDP), collagen deposition, and CTGF mRNA expression was higher in control or malnourished mice exposed to BPA than in the respective non-exposed groups. Nevertheless, mice fed LP diet exposed to BPA exhibited higher angiotensinogen and cardiac TGF-beta1 mRNA expression than mice treated with LP or BPA alone. Wall:lumen ratio and cross-sectional area of intramyocardial arteries were higher either in LP or BPA group compared with control mice. Taken together, our data suggest that short-term BPA exposure results in LV diastolic dysfunction and fibrosis and intramyocardial arteries inward remodeling, besides potentiate protein malnutrition-induced hypertension and cardiovascular risk.